2016
DOI: 10.1074/jbc.m115.685321
|View full text |Cite
|
Sign up to set email alerts
|

Regulatory Characteristics of Vibrio vulnificus gbpA Gene Encoding a Mucin-binding Protein Essential for Pathogenesis

Abstract: Binding to mucin is the initial step for enteropathogens to establish pathogenesis. An open reading frame, gbpA, of Vibrio vulnificus was identified and characterized in this study. Compared with wild type, the gbpA mutant was impaired in binding to mucin-agar and the mucin-secreting HT29-methotrexate cells, and the impaired mucin binding was restored by the purified GbpA provided exogenously. The gbpA mutant had attenuated virulence and ability of intestinal colonization in a mouse model, indicating that GbpA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
30
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 26 publications
(30 citation statements)
references
References 60 publications
0
30
0
Order By: Relevance
“…vulnificus strains integrate into marine aggregates (chitin) more efficiently than C-type strains. This study also found that expression of gbpA was significantly higher in C-type strains [20]. While more research is needed, it is clear that environmental context could be an important link to understanding V .…”
Section: Introductionmentioning
confidence: 68%
See 1 more Smart Citation
“…vulnificus strains integrate into marine aggregates (chitin) more efficiently than C-type strains. This study also found that expression of gbpA was significantly higher in C-type strains [20]. While more research is needed, it is clear that environmental context could be an important link to understanding V .…”
Section: Introductionmentioning
confidence: 68%
“…In fact, V . vulnificus GbpA is also a mucin-binding protein and is essential for pathogenesis in a mouse model [20]. Interestingly, a recent study found E-type V .…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, no genes encoding the PLAs have been identified from V. vulnificus, and thus the molecular mechanisms by which the bacterium modulates the expression of the genes have not yet been characterized. In the present study, we conducted a transcriptome analysis and identified the plpA gene, which is preferentially expressed in V. vulnificus cells exposed to human intestinal HT29-methotrexate (MTX) cells (10,11). The characteristics of V. vulnificus PlpA (VvPlpA), the product of plpA, were verified experimentally.…”
mentioning
confidence: 84%
“…Although a few examples of transcriptional coactivation of bacterial virulence genes by multiple activators have been reported (11,48), coactivation by HlyU and CRP has not yet been reported. Each HlyU and CRP binds to the upstream sequence of P plpA and activates the promoter as a solitary regulator, albeit not to levels comparable with that of the wild type (Figs.…”
Section: Characterization Of Plpa In V Vulnificusmentioning
confidence: 99%
See 1 more Smart Citation